Maritime-port technology and development - Kaura, Dipti; Kumar, Vishal (SCITUS Academics LLC, 2016)
A port is a location on a coast or shore containing one or more harbors where ships can dock and transfer people or cargo to or from land. Port locations are selected to optimize access to land and navigable water, for commercial demand, and for shelter from wind and waves. Maritime transport is the shipment of goods and people by sea and other waterways. Port operations are a necessary tool to enable maritime trade between trading partners. To ensure smooth port operations and to avoid congestion in the harbor it is inevitable to permanently upgrade the port's physical infrastructure, invest in human capital, fostering connectivity of the port and upgrade the port operations to prevailing standards. Hence, port operations can be distinct as all policies, reforms and regulations that influence the infrastructure and operations of port facilities including shipping services.